Oral health promotion practices: a survey of Florida child care center directors - Vinodh Bhoopathi; Ajay Joshi; Romer Ocanto; Robin J. Jacobs (BMC, 2018)
Abstract Background To understand the oral health promotion practices (OHPPs) in Florida licensed childcare centers (CCCs), we surveyed the childcare center directors (CCCDs) employed at these centers. We determined if CCC's affiliation with Early Head Start/Head Start (EHS/HS) programs was associated with the number of OHPPs implemented. Methods For this cross-sectional study we emailed a pretested 45-item online survey to unduplicated email addresses of 5142 licensed CCCDs as listed in the publicly available Florida Department of Child and Family services database. Univariate and bivariate analyses were conducted. In addition, a Poisson regression model predicting higher numbers of OHPPs implemented was conducted. Results A response rate of 19.4% was estimated. CCCDs reporting to implement a higher number of OHPPs in their CCCs were more likely to have longer work experience (b = 0.006, 95% CI: 0.001,0.012 p = 0.03), work in EHS/HS affiliated centers (b = 0.7, 95%CI: 0.48,0.91) p < 0.001), and have more positive attitudes about pediatric oral health (b = 0.08, 95%CI: 0.05, 0.10) p < 0.001). CCCDs with more self-perceived barriers reported implementing a lower number of OHPPs (b = − 0.046, 95% CI: -0.09, − 0.003 p = 0.035) compared to their counterparts. Conclusions A significant association between a CCC's affiliation with EHS/HS programs and the number of OHPPs implemented was observed. In addition, CCCD's years of experience, attitudes towards oral health, and self-perceived barriers in implementing OHPPs were also associated with the number of OHPPs implemented.